2017
DOI: 10.4103/ijnmr.ijnmr_216_16
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of nurses' empowerment in the management of patient aggression: A qualitative study

Abstract: Background:Patients’ aggression in the mental care setting is a global health problem with major psychological, physical, and economic consequences; nurse empowerment to manage this aggressive behavior is an important step in psychiatric nursing. The aim of this study was to explore psychiatric nurses’ experiences of the challenges of empowerment in the management of patients’ aggression.Materials and Methods:This qualitative study was performed among 20 nurses working in a major referral psychiatric center in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…Playful problem-solving was the most frequently identified way of coping among nurses who work in the Admission and Emergency Departments of Hospitals related to Shiraz University of Medical Sciences [25], which is very similar to our study findings. However, in contrast to our findings, results from a study that selected hospitals in Udupi and Mangalore districts of Karnataka showed that seeking social support was the most frequently employed mechanism to deal with stress, followed by Planned problem-solving [26].…”
Section: Stress (34%supporting
confidence: 90%
“…Playful problem-solving was the most frequently identified way of coping among nurses who work in the Admission and Emergency Departments of Hospitals related to Shiraz University of Medical Sciences [25], which is very similar to our study findings. However, in contrast to our findings, results from a study that selected hospitals in Udupi and Mangalore districts of Karnataka showed that seeking social support was the most frequently employed mechanism to deal with stress, followed by Planned problem-solving [26].…”
Section: Stress (34%supporting
confidence: 90%
“…According to the characteristics of the three dimensions described above, we may be able to pinpoint some personal characteristics and experiences for volunteers in order to excel in each activity. For example, helping the elderly proceed through several steps in a hospital may require a volunteer characterized by a high level of service orientation (e.g., Carraher, Parnell, Carraher, Carraher, & Sullivan, 2006;McBride, Mendoza, & Carraher, 1997) and self-control (e.g., Gholamzadeh, Sharif, & Rad, 2011;Tangney, Baumeister, & Boone, 2004). For the second dimension, volunteers who convey information and knowledge may need a set of characteristics (e.g., those that may encourage life-long learning; Jirgensons, 2015) which are different from those needed by volunteers who lead group exercises (e.g., creativity; Zimmermann, Dupree, & Hodges, 2014).…”
Section: Discussionmentioning
confidence: 99%

Polish Psychological Bulletin

Raveepatarakul,
Ngamake,
Srichaisawat
et al. 2020